Indonesia Digital Economic Diplomacy during the Covid-19 Global Pandemic - Triwahyuni, Dewi (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
The study aims to optimize the use of Information Technology in Indonesian diplomacy during the COVID-19 pandemic, especially in the economic sector. To analyze this phenomenon, the research uses qualitative methods. The study is analytical descriptive by collecting detailed data from various sources of information, especially from multiple sources related to the object of this study. The research results concluded that Indonesia does not have a clear agenda or blueprint for using digital diplomacy. Because the use of information technology to publish policies during the COVID-19 pandemic is increasing, Indonesia must continue to learn from many countries in introducing the formulation of an economic digital diplomacy agenda from institutional adaptation to new approaches in foreign policy socialization through new media. This research will impact a more comprehensive digital diplomacy model for Indonesia.